The mediating role of customer satisfaction in the relationship between service quality and customer loyalty in multi-channel retail banking - Shame Mugova; Nancy Gathoni Kiliswa; Margaret Mashizha (Cogent Business & Management, 2025)
This study examines the interrelationships among service quality (SQ), customer satisfaction (CS), and customer loyalty (CL) in the context of multi-channel retail banking. While customer satisfaction measures a customer’s present evaluation of service, customer loyalty reflects their long-term commitment to an organisation. Service quality assessment involves comparing perceived service delivery against customer expectations. Convenience sampling was used to obtain 466 responses from bank customers. Using structural equation modelling, this research analyses primary data from 466 bank customers in Durban, South Africa, using a self-administered questionnaire to investigate these relationships. A refined model demonstrates that service quality indirectly affects customer loyalty through customer satisfaction, reinforcing the importance of customer experience in multi-channel banking. Furthermore, the results show that satisfied customers demonstrate stronger bank allegiance in a multichannel banking environment. Unlike previous studies that focus on traditional banking models, this research investigates multichannel banking environments where customers interact across multiple platforms. This study contributes new insights into the mediating role of satisfaction in the service loyalty relationship, highlighting the importance of integrating service strategies. The findings provide actionable insights for banks aiming to enhance service quality across multiple channels.